Non‐chromate conversion process for zinc coating with durable hydrophobicity and enhanced corrosion resistance. Issue 3 (29th August 2022) - Chen, J. Y.; Hu, Z. Y.; Li, Z. X.; Wang, X. L.; Gu, C. D.; Tu, J. P.
Abstract: A Zn‐based coating with durable hydrophobicity and good corrosion resistance was formed on a mild steel substrate, which involves electroplating Zn from a non‐aqueous electrolyte, followed by passivation in an oleic acid (OA) solution. The electrodeposited Zn coatings were porous, which facilitated the formation of a chemical conversion layer of Zn oleate (ZO) during OA passivation. The Zn coating after passivation had a two‐layer structure, which included an outer layer of ZO with a thickness of ∼26 μm and an inner layer of Zn with a thickness of ∼6 μm. The outer layer ZO is a type of metal soap with a smooth surface and durable hydrophobicity, such that water droplets can easily slip off its surface. Corrosion testing and electrochemical measurements in 3.5 wt.% NaCl aqueous solution indicate that the Zn coating after OA passivation exhibits outstanding anti‐corrosion properties compared with those exhibited by pure Zn coating. The corrosion products and mechanism of the two‐layer coating were explored. This study shows that smooth metal oleate coatings can provide hydrophobicity and corrosion resistance simultaneously to mild steel substrates.